Phosphate solubilizing ability of two Arctic Aspergillus niger strains - Shiv Mohan Singh; Lal Sahab Yadav; Sanjay Kumar Singh; Purnima Singh; Paras Nath Singh; Rasik Ravindra (Polar Research, 2011)
Many filamentous fungi were isolated from the soils of Ny-Ålesund, Spitsbergen, Svalbard, and were screened in vitro for their phosphate solubilizing ability. Two strains of Aspergillus niger showed good tricalcium phosphate (TCP) solubilizing ability in Pikovskaya's medium. The TCP solubilization index was calculated at varying levels of pH and temperatures. The ability of Aspergillus niger strain-1 to solubilize and release inorganic-P was 285 µg ml–1, while Aspergillus niger strain-2 solubilized 262 µg ml–1 from 0.5% TCP after seven days. This is the first report of TCP solubilization by Arctic strains that may serve as very good phosphate solubilizers in the form of biofertilizer.